2020
DOI: 10.1002/jso.26320
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in low‐value surgical care and time to surgery in high‐volume hospitals

Abstract: BackgroundThe objective of this study is to examine racial differences in receipt of low‐value surgical care and time to surgery (TTS) among women receiving treatment at high‐volume hospitals.MethodsStage I–III non‐Hispanic Black (NHB) and Non‐Hispanic White (NHW) breast cancer patients were identified in the National Cancer Database. Low‐value care included (1) sentinel lymph node biopsy (SLNB) among T1N0 patients age ≥70 with hormone receptor–positive cancers, (2) axillary lymph node dissection (ALND) in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The reasons why those who identified as Black race, uninsured or Medicaid insured, and were of single marital status were less likely to receive surgical management is most likely due to a combination of disease presentation, patient preference, and surgeon recommendations. Black, uninsured, and Medicaid patients face barriers in receiving surgical care in the nonmetastatic setting, and we anticipate factors driving surgical access in MBC patients are similar [ 6 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons why those who identified as Black race, uninsured or Medicaid insured, and were of single marital status were less likely to receive surgical management is most likely due to a combination of disease presentation, patient preference, and surgeon recommendations. Black, uninsured, and Medicaid patients face barriers in receiving surgical care in the nonmetastatic setting, and we anticipate factors driving surgical access in MBC patients are similar [ 6 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multivariable analysis was performed using age, race, insurance status, marital status, neighborhood socioeconomic status, region of care delivery, chemotherapy status, and number of metastatic sites as independent variables to determine the odds of undergoing surgery. Independent variables were selected based on their association or recommendations to be considered for surgical decision making [ 6 , 14 , [21] , [22] , [23] , [24] , [25] ]. Odds ratios were reported along with the Wald Chi-Square tests.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging studies suggest minority‐serving cancer centers with high‐volume breast cancer cases tend to have similar uptake of clinical trial guidelines compared to academic facilities 26,28,29 . For instance, Jackson et al showed no racial differences in receipt of ALND among women meeting ACOSOG Z0011 criteria receiving treatment in high volume centers in the National Cancer Database 30 . On the other hand, other studies have shown people who face difficulties in accessing oncologic care such as people of color, uninsured patients, individuals with lower levels of education or income are more likely to have ALND over SLNB despite current guidelines 28,31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…26,28,29 For instance, Jackson et al showed no racial differences in receipt of ALND among women meeting ACOSOG Z0011 criteria receiving treatment in high volume centers in the National Cancer Database. 30 On the other hand, other studies have shown people who face difficulties in accessing oncologic care such as people of color, uninsured patients, individuals with lower levels of education or income are more likely to have ALND over SLNB despite current guidelines. 28,[31][32][33] Similarly, our findings of an association between decreasing nSES and increasing ALND use suggest place of residence may have implications for receipt of some low value breast surgical oncology procedures.…”
Section: Low Value Surgical Carementioning
confidence: 99%
“…77 A recent evaluation of time to surgery among patients with stage I to III breast cancer in a national hospital-based registry showed 30% of non-Hispanic Black patients underwent surgery more than 60 days after diagnosis, compared with 18% of non-Hispanic White women. 78 Delay in time to surgery among Black women warrants additional investigation, because Black patients with breast cancer have a higher mortality rate compared with their White counterparts. 79 For surgeons in particular, racial disparities in time to surgery warrant additional knowledge and understanding.…”
Section: Factors Contributing To Surgical Delaymentioning
confidence: 99%